Tyrosine kinase inhibitors targeting vascular endothelial growth factor and the risk of aortic dissection-A pharmacovigilance analysis - Michael Dörks; Kathrin Jobski; Stefan Herget‐Rosenthal; Falk Hoffmann; Antonios Douros (Wiley, 2021)
Abstract There are concerns by the United States Food and Drug Administration (FDA) regarding a potential link between tyrosine kinase inhibitors targeting vascular endothelial growth factor (VEGF‐TKIs) and the risk of aortic dissection. Elevation of blood pressure induced by VEGF‐TKIs has been discussed as part of the pathomechanism. To address this important safety issue, we conducted a large pharmacovigilance study assessing the risk of aortic dissection reporting associated with the use of VEGF‐TKIs, thereby exploring the role of blood pressure. We queried the FDA Adverse Event Reporting System from 2004 to 2019 for reports including VEGF‐TKIs and aortic dissection and estimated reporting odds ratios (RORs) and 95% confidence intervals (CIs) of aortic dissection associated with the use of VEGF‐TKIs. Secondary analyses stratified by the strength of blood pressure elevation (≥10 mmHg vs. <10 mmHg increased systolic or diastolic bloods pressure) and pre‐existing arterial hypertension. There were 81 reports of aortic dissection related to VEGF‐TKIs during the study period. VEGF‐TKIs were associated with an increased risk of aortic dissection reporting (ROR, 4.31; 95% CI, 3.43 to 5.42). The risk was higher among compounds strongly increasing blood pressure (ROR, 5.33; 95% CI, 3.88 to 7.32) than among compounds moderately increasing blood pressure (ROR, 2.79; 95% CI, 1.83 to 4.27). Pre‐existing arterial hypertension did not modify the association. Overall, our study showed an increased risk of aortic dissection reporting associated with the use of VEGF‐TKIs. Blood pressure elevation seems to play a role in the pathophysiology of this adverse effect.